Feed consumption and feed conversion ratio of eight weeks old male local ducks treated with santoquin and vitamin E supplement - Purba, Maijon; Ketaren, Pius. P. (Indonesian Animal Sciences Society, 2011)
The aim of this experiment was to investigate the effectiveness of santoquin (Sq) and vitamin E (VE) as feed additives to improve performance of male local ducks. The experiment was conducted using a completely randomized design. Two hundred and eighty male day old ducks (dod) of male Mojosari Alabio crosbred ducks were allocated to ten treatments with four replicates and seven ducks/replicate. The experimental diets were: Basal-diet (RO) without antioxidant (RB) (control); RB + 50 ppm santoquin (Sq) + 100 IU vitamin E (VE) (R1); RB + 50 ppm Sq + 200 IU VE (R2); RB + 50 ppm Sq + 300 IU VE (R3); RB + 100 ppm Sq + 100 IU VE (R4); RB + 100 ppm Sq + 200 IU VE (R5); RB + 100 ppm Sq + 300 IU VE (R6); RB + 150 ppm Sq + 100 IU VE (R7); RB + 150 ppm Sq + 200 IU VE (R8); RB + 150 ppm Sq + 300 IU VE (R9). The ducks were fed ad libitum for 8 weeks. Parameters observed were: feed consumption, live weight, body weight gain, feed conversion rate (FCR) and mortality. The results showed that Sq and VE supplementation did not significantly affect (P > 0.05) the feed consumption, live weight, body weight gain, feed conversion ratio and mortality rate of the ducks. This experiment shows that santoquin andÂ vitamin E supplementation did not affect the performance of male local MA ducks. Key Words: Feed Consumtion, Feed Conversion Ratio, Santoquin, Vitamin E, Local Ducks